FAKTOR DALAM PENGAMBILAN KEPUTUSAN ETIS OLEH KONSULTAN PAJAK: INDIVIDUAL DAN SITUASIONAL - Ni Made Ayu Dwi Lentari Dewi; Kadek Trisna Dwiyanti (Universitas Pendidikan Nasional, 2018)
Factors in Ethical Decision Making By Tax Consultants: Individual and Situational. The purpose of this research is to find the effect of professional ethics, machiavellianism, and risk preferences on ethical decision making by tax consultants. The independent variable in this study is the Perception of Professional Ethics, Machiavellianism and Risk Preference, while Ethical Decision Making is the dependent variable. The research used a quantitative approach with data collection methods through questionnaires. The sample used was 100 tax consultants registered at the IKPI Bali Branch. Data analysis using multiple linear regression. The results showed that the Perception of Professional Ethics, Machiavellianism, and Risk Preference together had a significant effect on Ethical Decision Making. The Perception of Professional Ethics partially has a positive and significant effect on Ethical Decision Making. Machiavellianism partially has a negative and significant effect on Ethical Decision Making. While the Risk Preference partially has a negative and significant effect on Ethical Decision Making. The results of testing the coefficient of determination indicate that the Perception of Professional Ethics, Machiavellianism, and Risk Preference together have an effect of 73.9% on Ethical Decision Making by Tax ConsultantsKeywords: Perception of Professional Ethics, Machiavellianism, Risk Preference, Ethical Decision Making, Tax Consultants